The cutaneous beta human papillomavirus type 8 E6 protein induces CCL2 through the CEBPα/miR-203/p63 pathway to support an inflammatory microenvironment in epidermodysplasia verruciformis skin lesions - Vella, Luca; Sternjakob, Anna; Lohse, Stefan; Fingerle, Alina; Sperling, Tanya; Wickenhauser, Claudia; Stöckle, Michael; Vogt, Thomas; Roemer, Klaus; Ołdak, Monika; Smola, Sigrun (Frontiers in Cellular and Infection Microbiology, 2024)
Human papillomavirus type 8 (HPV8), a cutaneous genus beta HPV type, has co-carcinogenic potential at sun-exposed sites in patients suffering from the inherited skin disease epidermodysplasia verruciformis (EV). We had previously shown that Langerhans cells responsible for epithelial immunosurveillance were strongly reduced at infected sites, and that the HPV8 E7 protein interferes with the CCAAT/enhancer-binding protein (C/EBP)β to suppress the Langerhans cell chemokine CCL20. At the same time, however, we observed that the stromal compartment of EV lesions is are heavily infiltrated with inflammatory immune cells, which is similar to the situation in HPV8 E6 transgenic mice. To identify critical inflammatory factors, we used an unbiased multiplex approach, hat formatiert: Englisch (Vereinigte Staaten